Enhancement of β-carotene-rich carotenoid production by a mutant Sporidiobolus pararoseus and stabilization of its antioxidant activity by microencapsulation - Atchara Manowattana (2020)
© 2020 Wiley Periodicals LLC. The effective enhancement of β-carotene production by Sporidiobolus pararoseus KM281507 was successfully achieved by random mutagenesis using ethyl methanesulfonate (EMS) combined with light irradiation. The mutant S. pararoseus E47 obtained from EMS mutagenesis produced a promising yield of biomass, β-carotene, and total carotenoids under white light (1,000 Lux). The maximal biomass (19.76 g/L), β-carotene (128.97 mg/L), total carotenoids (179.72 mg/L), and β-carotene content (72%, w/w) of the total carotenoids were obtained. The β-carotene-rich carotenoids were extracted from yeast cells and encapsulated in alginate beads using a new encapsulation method to enhance its stability, revealing an effective concentration of 0.5% alginate + 1.0% vitamin C. The half-life of this β-carotene was 13 and 68 days for un-encapsulated and encapsulated + 1.0% vitamin C at 4°C with 1,000-Lux light irradiation, respectively. This result could uncover a potential alternative β-carotene source and its further application in foods, animal feeds, and cosmetic industries. Practical applications: The carotenoid extract of S. pararoseus mutant E47 was rich in β-carotene (72%, w/w). After extraction, the β-carotene-rich carotenoids were very sensitive to light and oxygen; thus, they were stabilized using a microencapsulation technique. To enhance their stability, vitamin C was added in the alginate phase making the β-carotene-rich carotenoid alginate beads (BCAB) highly stable and simply used for many applications including foods, feeds, cosmetics, and medicines.